2020
DOI: 10.3168/jds.2020-18265
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of non-aureus staphylococci from quarter milk, teat apices, and rectal feces of dairy cows, and their virulence potential

Abstract: Non-aureus staphylococci (NAS) are predominantly isolated from bovine milk samples of quarters suffering from subclinical mastitis. They are also abundantly present on dairy cows' teat apices and can be recovered from bovine fecal samples, as recently described. Differences in ecology, epidemiology, effect on udder health, and virulence or protective traits have been reported among the species within this group. The objectives of this study were (1) to describe the species-specific distribution of NAS in 3 bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…The phenotypically different Gram-positive, catalasepositive cocci found between D-35/D-21 and L6 that were stored at -80 °C, were identified at the species level by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS (MALDI Biotyper, Bruker Daltonics, Bremen, Germany) [39]. A score value ≥ 2.000 was considered reliable at species level for most species although this was lowered to 1.700 for the species-level identification of NAS isolates as previously described [39,40], and a validated and updated bovine NAS library was used [5]. If isolates could not be reliably identified by MALDI-TOF MS, 16S rRNA sequencing was carried out [41].…”
Section: Maldi-tof Mass Spectrometry and Multilocus Sequence Typingmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypically different Gram-positive, catalasepositive cocci found between D-35/D-21 and L6 that were stored at -80 °C, were identified at the species level by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS (MALDI Biotyper, Bruker Daltonics, Bremen, Germany) [39]. A score value ≥ 2.000 was considered reliable at species level for most species although this was lowered to 1.700 for the species-level identification of NAS isolates as previously described [39,40], and a validated and updated bovine NAS library was used [5]. If isolates could not be reliably identified by MALDI-TOF MS, 16S rRNA sequencing was carried out [41].…”
Section: Maldi-tof Mass Spectrometry and Multilocus Sequence Typingmentioning
confidence: 99%
“…Non-aureus staphylococci (NAS) are the most frequently isolated bacteria from bovine mammary quarters either with or without subclinical mastitis [1][2][3][4][5] and have been detected in dry quarter secretions as well [6,7]. Differences in ecology, epidemiology and relevance for bovine udder health in this heterogeneous group of bacteria are present both at the species level and within species [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…De Visscher, 2 * T. L'Abee-Lund, 1 C. Ngassam Tchamba, 3 J. G. Mainil, 3 D. Thiry, 3 S. De Vliegher, 2 and Y. Wasteson 1 † samples is described in several studies; however, the results are not directly comparable due to a variety of study designs. A recent study from Belgium concluded that the 5 most prevalent NAS species recovered from quarter milk samples were Staphylococcus chromogenes, Staphylococcus haemolyticus, Staphylococcus equorum, Staphylococcus hominis, and Staphylococcus cohnii (Wuytack et al, 2020). In Norway, Staphylococcus epidermidis and Staph.…”
Section: Introductionmentioning
confidence: 99%
“…The NAS species lack the aggressive potential of Staph. aureus, and less is known about the virulence of these species (Becker et al, 2014;Naushad et al, 2019;Wuytack et al, 2020). Knowledge regarding virulence of both Staph.…”
Section: Introductionmentioning
confidence: 99%
“…together and treated them as a single group. While there is an increasing body of evidence to suggest that all NAS are not equal (Valckenier et al, 2020;Wuytack et al, 2020), we took this approach to facilitate comparison with earlier research in the area. A more detailed analysis of the outcomes and potential roles of the individual NAS spp.…”
Section: Discussionmentioning
confidence: 99%